2017
DOI: 10.1002/cjce.22876
|View full text |Cite
|
Sign up to set email alerts
|

Transient analysis of the steam‐water direct contact condensation in the packed column

Abstract: The transient heat transfer behaviour of direct contact condensation of steam in spray cooling water in a packed column was investigated experimentally and theoretically in this work for the first time. A new analysis method of the state equation was applied to analyze the molar quantity variation of steam in the course of the experiment. The results showed that increasing the cooling water flow rate properly could significantly accelerate the steam condensation rate and this was more obvious at the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…where p actÀ4 is the actual pressure of steam to the fourth turbine extraction, T actÀ4 is the actual temperature of the steam to the fourth turbine extraction, and h actÀ4 is the actual specific enthalpy of the steam to the fourth turbine extraction. In a similar way, calculation unit 1 also calculates the actual specific enthalpy value of the exhaust steam from the ST: (8) where p actÀex is the actual pressure of the exhaust steam from the ST, x ex is dryness of the exhaust steam from the ST, and h extÀex is the actual specific enthalpy of the exhaust steam from the ST. Calculation unit 1 then also calculates the actual power of the ST low-pressure cylinder 35,36 :…”
Section: Presentation Of Calculation Unit 1 Actual Turbine Powermentioning
confidence: 99%
See 1 more Smart Citation
“…where p actÀ4 is the actual pressure of steam to the fourth turbine extraction, T actÀ4 is the actual temperature of the steam to the fourth turbine extraction, and h actÀ4 is the actual specific enthalpy of the steam to the fourth turbine extraction. In a similar way, calculation unit 1 also calculates the actual specific enthalpy value of the exhaust steam from the ST: (8) where p actÀex is the actual pressure of the exhaust steam from the ST, x ex is dryness of the exhaust steam from the ST, and h extÀex is the actual specific enthalpy of the exhaust steam from the ST. Calculation unit 1 then also calculates the actual power of the ST low-pressure cylinder 35,36 :…”
Section: Presentation Of Calculation Unit 1 Actual Turbine Powermentioning
confidence: 99%
“…Moreover, Pereira et al 7 optimized the shell and tube of the horizontal condenser. Hu et al, 8 on the other hand, presented in their article a transient analysis of the direct contact condensation. Strušnik et al 9 analyzed the effect of noncondensing vapor on the condenser heat transfer and found that noncondensable gases concentrate around the cooling pipes, thus significantly reducing heat transfer.…”
Section: Introductionmentioning
confidence: 99%